# Find the zeros of the polynomial x2 – 3x – m (m + 3).

We have,

f (x) = x2 – 3x – m (m + 3)

Now, by adding and subtracting px, we get

f (x) = x2 - mx - 3x + mx – m (m + 3)

= x [x – (m + 3)] + m [x – (m + 3)]

= [x - (m + 3)] (x + m)

f (x) = 0

[x - (m + 3)] (x + m) = 0

[x - (m + 3)] = 0 or (x + m) = 0

x = m + 3 or x = - m

Hence, the zeros of the given polynomial are - m and m + 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Champ Quiz |Revealing the relation Between Zero and Coefficients38 mins  Relation Between zeroes and Coefficients46 mins  Interactive Quiz - Geometrical Meaning of the Zeroes32 mins  Relationship between Zeroes and Coefficients-238 mins  Relation b/w The Zeroes and Coefficients of Cubic Polynomials54 mins  Revision of Relation Between the Zeroes and Coefficients of Quadratic Polynomial46 mins  Relationship between Zeroes and Coefficients-152 mins  Quiz - Division Algorithm38 mins  Interactive Quiz:Polynomials43 mins  Division Algorithm-130 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 